A Prospective Observational Study Comparing Long-Course Conventional Neoadjuvant Chemoradiotherapy with Short-Course Radiotherapy Followed by Consolidation Chemotherapy with Delayed Surgery in Locally Advanced Rectal Cancer - Thakur, Niketa; Seam, Rajeev K.; Gupta, Manoj K.; Gupta, Manish; Fotedar, Vikas; Vats, Siddharth; Rana, Sakshi; Vias, Poorva; Ahuja, Rachit (South Asian Journal of Cancer, 2020)
Background Polish and Australian randomized studies compared short-course radiotherapy (RT) with immediate surgery and long-course chemoradiotherapy (CRT) with delayed surgery. In these studies, similar long-term survival and local control have been reported for both these approaches, but pathological complete response (pCR) is not better with short-course RT. Moreover, studies have shown better tumor downstaging with delayed surgery. In this context, the use of short-course RT with delayed surgery may have some advantages and needs to be tested in clinical trials.Patients and Methods This was a two-arm, prospective, observational study, in which preoperative short-course RT followed by two cycles of chemotherapy was compared with the conventional neoadjuvant CRT in locally advanced rectal cancer. The primary end points were the rate of complete response and toxicity profile. The secondary end points were the rate of R0 resection, overall survival, and progression-free survival. The data obtained from the two arms were analyzed using Pearson’s chi-square test to determine the statistical significance between the two treatment arms.Results The pCR rate was 6.7% in the study arm and 0 in the control arm (p = 0.343). The RO resection rates were 92.8 and 92.3% in the study and control arms, respectively. The rates of grade 3and 4 acute toxicity in the study and control arms were 14.2 and 61.5%, respectively (p = 0.011). The rates of grade 3 and 4 late toxicity in the study and control arms were 21.4 and 15.3%, respectively (p = 0.686).Conclusions The pCR rates and the late toxicities in both arms are comparable. The major advantages of the 5 × 5 Gy regimen with chemotherapy in a neoadjuvant setting are a significant reduction in acute toxicities and better patient compliance along with similar efficacy as that of the standard regimen.
Keywords: chemoradiotherapy; rectal neoplasm; short-course RT